2017
DOI: 10.1371/journal.pone.0187330
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate mofetil prevents the delayed T cell response after pilocarpine-induced status epilepticus in mice

Abstract: Growing clinical and laboratory evidence corroborates a role for the immune system in the pathophysiology of epilepsy. In order to delineate the immune response following pilocarpine-induced status epilepticus (SE) in the mouse, we monitored the kinetics of leukocyte presence in the hippocampus over the period of four weeks. SE was induced following a ramping protocol of pilocarpine injection into 4–5 weeks old C57BL/6 mice. Brains were removed at days 1–4, 14 or 28 after SE, and the hippocampi were analyzed v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…As animals differ in their tolerance to pilocarpine, this method ensures that animals are not unnecessarily given high doses and improves the induction probability. These results were also observed in several other studies using both pilocarpine and LiCl-pilocarpine models ( Brandt et al., 2010 ; Leung et al., 2015 ; Neumann et al., 2017 ; Wu and Wang, 2018 ).…”
Section: The Limitations Strike Back: Imperfections In the Lithium-pisupporting
confidence: 87%
See 1 more Smart Citation
“…As animals differ in their tolerance to pilocarpine, this method ensures that animals are not unnecessarily given high doses and improves the induction probability. These results were also observed in several other studies using both pilocarpine and LiCl-pilocarpine models ( Brandt et al., 2010 ; Leung et al., 2015 ; Neumann et al., 2017 ; Wu and Wang, 2018 ).…”
Section: The Limitations Strike Back: Imperfections In the Lithium-pisupporting
confidence: 87%
“…This however was not fruitful in all animal models. For example, studies have administered single injections of 100 mg/kg of pilocarpine intraperitoneally to induce SE in mice, with the total dosage reaching up to 800 mg/kg ( Neumann et al., 2017 ). Even with such a high overall dose, only 54% of the animals survived the procedure and developed SE.…”
Section: The Pilocarpine Model: the Early Daysmentioning
confidence: 99%
“…. due to overt behavioral seizure activity the experimenter could not be blinded to whether the animal was injected with pilocarpine or with saline' [86].…”
Section: Item 5-examplementioning
confidence: 99%
“…A recent experiment showed a biphasic increase of CD45 + immune cells in the hippocampus was implicated in innate macrophages during the first four days as well as CD3 + T-lymphocytes at 28 days following pilocarpine-induced SE. Correspondingly, one study has suggested pilocarpineinduced SE of C57BL/6 mice leads to either the infiltration of activated macrophages into the hippocampus or activation of resident glial cells, which are predicted to induce a proinflammatory immune response that may attract more immune cells and allow T-lymphocytes to enter the CNS by affecting the permeability of the BBB [52]. Infiltrated T-cell then an attack on distinct hippocampal neurons sufficient to make a contribution to cellular and structural dynamics that displayed signs of limbic encephalitis that induced TLEhippocampal sclerosis (HS) [53].…”
Section: T-lymphocytesmentioning
confidence: 99%